2020
DOI: 10.3390/plants9040407
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin: Awakening the Defense Mechanisms during Plant Oxidative Stress

Abstract: Melatonin is a multifunctional signaling molecule that is ubiquitously distributed in different parts of a plant and responsible for stimulating several physio-chemical responses to adverse environmental conditions. In this review, we show that, although plants are able to biosynthesize melatonin, the exogenous application of melatonin to various crops can improve plant growth and development in response to various abiotic and biotic stresses (e.g., drought, unfavorable temperatures, high salinity, heavy metal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(97 citation statements)
references
References 124 publications
(236 reference statements)
1
82
0
Order By: Relevance
“…This compound is a multifunctional molecule distributed in different parts of plants and involved in several physiological processes: the circadian rhythm, photosynthesis, biomass production, root development, seed germination, fruit ripening, foliar senescence, membrane integrity, redox network, osmoregulation and response to abiotic stress ( Khan et al, 2020 ). Several works have shown that exogenous application of melatonin can increase plant growth and resistance to stress.…”
Section: Amino Acids and Other N -Containing Compomentioning
confidence: 99%
See 2 more Smart Citations
“…This compound is a multifunctional molecule distributed in different parts of plants and involved in several physiological processes: the circadian rhythm, photosynthesis, biomass production, root development, seed germination, fruit ripening, foliar senescence, membrane integrity, redox network, osmoregulation and response to abiotic stress ( Khan et al, 2020 ). Several works have shown that exogenous application of melatonin can increase plant growth and resistance to stress.…”
Section: Amino Acids and Other N -Containing Compomentioning
confidence: 99%
“…It was suggested that the protective role of melatonin is due to the regulation of the antioxidant defence system, from direct ROS scavenging by reaction with H 2 O 2 , O 2 – , and OH ⋅ , to an increase in the activity of antioxidant enzymes (CAT, SOD, and GPX), as well as enzymes of the ascorbate-glutathione cycle (ascorbate peroxidase, monodehydroascorbate reductase, dehydroascorbate reductase, and glutathione reductase). It is also involved in the effects of non-enzymatic antioxidants (carotenoids, tocopherols, ascorbate, reduced glutathione, and phenolic compounds) ( Khan et al, 2020 ).…”
Section: Amino Acids and Other N -Containing Compomentioning
confidence: 99%
See 1 more Smart Citation
“…Removal of excessive accumulated ROS within cells through increased antioxidant system activity is a crucial protective mechanism in stress‐exposed plants. Previous researches demonstrated that under stress condition, melatonin acts as an antioxidant at cellular level to alleviate ROS and indirectly activates the gene expression of antioxidant enzymes (Arnao & Hernández‐Ruiz, 2019a, 2019b; Khan et al, 2020; Moustafa‐Farag et al, 2019). We also hypothesized that melatonin functions at the gene level to enhance expression of antioxidant enzymes, and their protective effect.…”
Section: Discussionmentioning
confidence: 99%
“…I have received many excellent manuscripts that try to shed some light on the potential mechanism of action of antioxidants and also described the identification of new compounds, bringing to the collection nine articles [ 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 , 15 ] and two reviews [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%